Validation of a questionnaire for the evaluation of clinical competencies in nutrition - Bretón de la Loza Martín, Mauricio; Guerrero Ceh, Jaqueline Guadalupe; Zúñiga Hernández, Ofmara Yadira; Cervantes Ramírez, Laura Tatiana; Garduño Díaz, Sara Diana; Carranco Gómez, Sonalí; Terrazas Meraz, María Alejandra (International Journal of New Education, 2019)
Today’s educational challenges require linking theory and practice in real settings to ensure meaningful learning and to respond to the social commitment of higher education institutions. At the Universidad Autónoma del Estado de Morelos (UAEM), nutrition studies follow the competency-based educational model. It is thus important to know the level of basic clinical competencies (Clinical History, Physiopathology, Procedures) that students of the Bachelor’s Degree in Nutrition have. Objective: To validate an instrument that allows the evaluation of the level of basic clinical competencies acquired by the students enrolled in the Degree in Nutrition. Design and methodology: This is an analytical cross-sectional observational study. All students enrolled at the beginning of the PAR-2018 semester (N=1018) were included as target population. The sample size was calculated by the formula for obtaining proportions with correction for finite population proposed in Daniel’s book (2005), yielding as a minimum size a n=280 students, to potentiate the statistical study all students surveyed were included. In the first instance, the instrument was validated through 5 academicpairs using the Delphi system, the reliability through Cronbach’s alpha and the main component tests for the exploratory factorial analysis and Spearman’s for the confirmatory analysis. In order to validate the linear relationship with the semester studied, ANOVA and Bonferroni were used, based on the use of the statistical program Stata® v.14. Results: The questionnaire was applied to 622 students from first to eighth semester, 469 (75.4%) are women and 153 (24.6%) are men. The reliability of the scales resulted with Chronbach Alphas greater than 0.7. Conclusions The validated proposal of a questionnaire to evaluate clinical competencies is presented to students of Bachelor in Nutrition.